SISTEM PENGELOLAAN SAMPAH TERPADU (SIPENGESTU) KELURAHAN SERENGAN DALAM KAJIAN SOSIOLOGI HUKUM - Mulyanto, Mulyanto (PARENTAL, 2013)
Implementation activities have been carried out by stages Sipengestu First, Waste Management Management Training with experts presenting organization. Second, training of Organic Waste Composting by presenting officials Ngudi Neat Governmental Group of Gergunung, North Klaten, Klaten ; Third, Waste Management Comparative Study on Self-Help Groups Neat community Ngudi Klaten in order to see first hand the waste management process integrated with the production process and potinisasi fertilizers that run for this , and the fourth , Facilitation Assistance in order training materials and knowledge that has been given can be applied to both . The results of the evaluation activities have been conducted through a questionnaire in training Sipengestu interesting data obtained as follows. First, calculate the percentage of the majority of participants expressed satisfaction tehadapa IBM program by 90 %, consisting of 66 % strongly agreed, while 24 % agree and 10 % disagree rest . Second , from the aspects of training management benefits that the management of garbage through the Sipengestu provide real benefits for the community Serengan by referring the results of the evaluation sheet by 66 % .